ANALISIS KEPEMIMPINAN PEREMPUAN DI INDONESIA MENGGUNAKAN METODE BIBLIOMETRIK - Tanjung, Sherlinda Fadhillah; Rusadi, Najwa Apriliana; Puteri, Kahlia Rahma; Alif, Muhammad Ikhsan (JURSIMA, 2023)
This study analyzes women's leadership in Indonesia using bibliometric methods to identify trends, collaborations, and related study focuses. By analyzing 61 relevant journals, this study found that women's leadership is dominated by charismatic, transformational, and participatory styles. The study also shows that the education sector is the largest space for women to lead, followed by the government, public, and industrial sectors. Factors that influence women's leadership include organizational culture, social support, and gender barriers. The results of this study not only contribute to scientific literature but also become a basis for policies and strategies to support women's leadership in various sectors.